A Synthesis of Blockchain Technology Research and the Design of a Conceptual Framework for Educational Document Management: A Case Study of Thonburi University - ฤกษ์สมุทร ปฐมพงษ์; เชื่อมสุข ปณัญภพ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to synthesize the concepts and mechanisms of permissioned blockchain technology integrated with decentralized storage systems to propose a conceptual framework for developing a digital educational document management system for Thonburi- University. The primary objectives are to prevent diploma forgery and unauthorized data tampering, as well as to develop an instant verification process through smart contracts within an architecture that fully complies with the Personal Data Protection Act (PDPA). The study employs a qualitative research methodology via documentary research, collecting data from international academic databases, namely IEEE, ScienceDirect, and Google Scholar (2018–2025). The data were systematically screened in accordance with the PRISMA Diagram, yielding 15 high-quality articles for comparative analysis. The results indicate that integrating a permissioned blockchain, specifically Hyperledger Fabric, with IPFS and smart contracts is the most effective approach. The system transitions to a decentralized model by storing the original files separately in IPFS and recording only the "hash values" on the blockchain, rendering the data immutable. Furthermore, smart contracts enable external organizations to instantly verify educational credentials within seconds by scanning a QR Code, which significantly reduces time and costs. Additionally, the system strictly implements data access control in compliance with PDPA regulations. In conclusion, the proposed architecture exhibits a high level of technical feasibility and can definitively resolve the issue of document forgery. It is ready to serve as a "blueprint" for developing a prototype, transitioning Thonburi University into a secure, globally recognized, and sustainable digital university.